Beispiel Nr: 04
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 9 x -2 y =1\\ -3 x -3 y = -7 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad 9 x -2 y =1\\ II \qquad -3 x -3 y = -7 \\ I \qquad 9 x -2 y =1 \qquad / \cdot\left(-1\right)\\ II \qquad -3 x -3 y = -7 \qquad / \cdot\left(-3\right)\\ I \qquad -9 x +2 y =-1\\ II \qquad 9 x +9 y = 21 \\ \text{I + II}\\ I \qquad -9 x +9 x+2 y +9 y =-1 +21\\ 11 y = 20 \qquad /:11 \\ y = \frac{20}{11} \\ y=1\frac{9}{11} \\ \text{y in I}\\ I \qquad 9 x -2\cdot 1\frac{9}{11} =1 \\ 9 x -3\frac{7}{11} =1 \qquad / +3\frac{7}{11} \\ 9 x =1 +3\frac{7}{11} \\ 9 x =4\frac{7}{11} \qquad / :9 \\ x = \frac{4\frac{7}{11}}{9} \\ x=\frac{17}{33} \\ L=\{\frac{17}{33}/1\frac{9}{11}\} \end{array} & \begin{array}{l} \\I \qquad 9 x -2 y =1\\ II \qquad -3 x -3 y = -7 \\ I \qquad 9 x -2 y =1 \qquad / \cdot\left(-3\right)\\ II \qquad -3 x -3 y = -7 \qquad / \cdot2\\ I \qquad -27 x +6 y =-3\\ II \qquad -6 x -6 y = -14 \\ \text{I + II}\\ I \qquad -27 x -6 x+6 y -6 y =-3 -14\\ -33 x = -17 \qquad /:\left(-33\right) \\ x = \frac{-17}{-33} \\ x=\frac{17}{33} \\ \text{x in I}\\ I \qquad 9 \cdot \frac{17}{33} -2y =1 \\ -2 y +4\frac{7}{11} =1 \qquad / -4\frac{7}{11} \\ -2 y =1 -4\frac{7}{11} \\ -2 y =-3\frac{7}{11} \qquad / :\left(-2\right) \\ y = \frac{-3\frac{7}{11}}{-2} \\ y=1\frac{9}{11} \\ L=\{\frac{17}{33}/1\frac{9}{11}\} \end{array} \end{array} $